Fonologi bahasa Lundayeh di Sabah - YWP Taringan, SMD Robert (Jurnal Bahasa; Vol 8 No 1 (2008): Jurnal Bahasa Volume 8 Number 1 June 2008, 2008)
Lundayeh language is one of the languages used by one of the natives in Sabah. Not much researches and studies have been done towards the language especially in the Malay languages. This journal discussed certain aspect related to the language such as in phonetic and phonology of the language which covered the vowels, consonants and diphthong. The Sabah Lundayeh language has six vowels, 19 consonants and five diphtongs. I would like to highlight a few special features of the Lundayeh language which has been identified and to show the differences compared to other natives language. Overall, I used the pronounce of consonant /p/ even the speaker (Lundayeh Kemaloh language) used the consonant /f/ to replace the pronounce of consonant /p/, for examples /pekaak/ or /fekaak/ means morning, and the word /yapeh/ or /yafeh/ means where. The difference do not indicate any change in the meaning as in other languages, there are also free variation. This will be further discussed in detailed under the sub-topic of the special features (characteristics) of Lundayeh language.